Lampung Local Wisdom as a Pedagogical Anchor: Developinga ‎Tourism History Textbook for Indonesian History Education - Yustina Sri Ekwandari; Aprilia Triaristina; Valensy Rachmedita; Ema Agustina (JPI: Jurnal Pustaka Indonesia, 2026)
This study addressed the limited availability of university-level Indonesian Tourism History textbooks that systematically integrate Lampung local wisdom, which restricts students’ engagement with regional cultural heritage. It aimed to develop and assess the feasibility of a textbook using the ADDIE model. A research and development design was implemented at the History Education Study Program, Universitas Lampung, involving 27 students enrolled in the Indonesian Tourism History course and two expert validators. Data were collected through semi-structured interviews, validator assessment rubrics, and a 13-item student-response questionnaire using a four-point Likert scale. Data were analyzed using feasibility percentages, descriptive statistics, the Intraclass Correlation Coefficient, and one-way ANOVA followed by Tukey HSD post hoc testing. The questionnaire showed acceptable internal consistency (Cronbach’s α = .701), while agreement between validators was excellent (ICC = .931). The textbook obtained feasibility scores of 86.3% and 83.0% from the two validators, both categorized as very good. Students reported a positive overall response (M = 3.05/4.00; feasibility index = 76.3%). Significant differences were found among student-response indicators, F(12, 338) = 2.450, p = .005; local-wisdom information exploration and local-wisdom knowledge received significantly higher ratings than active textbook use. These findings indicate that the ADDIE-developed textbook is a valid and practically feasible resource for integrating Lampung cultural heritage into higher education history learning. However, the findings are limited to one course cohort and perception-based data; future studies should involve larger multisite samples and quasi-experimental pretest–posttest designs to examine learning gains and creativity outcomes.